دراسة تحليلية لتنافسية الاقتصاد السوري - خضور رسلان; شبانة نادية (Latakia University Journal - Economic and Legal Sciences Series, 2017)
في ظل التطورات المتسارعة التي يشهدها العالم من عولمة واندماج نحو الاقتصاد العالمي والتطورات الكبيرة في تقانة المعلومات والاتصالات، أخذ مفهوم التنافسية يحظى باهتمام واسع، وعليه فقد أخذت الدول النامية منها والعربية تهيئ نفسها للتوائم مع هذه التطورات لأجل الاستفادة من مزاياها خاصة بانتهاج سياسات، وإصلاحات تهيئ بيئتها الاقتصادية المناسبة لتعزيز قدراتها التنافسية في عالم مفتوح أمام التجارة وأمام الاستثمارات الأجنبية. وعلى هذا الأساس قامت سورية بتبني مفهوم التنافسية بهدف الارتقاء بمستوى أداء المؤسسات العامة وقطاع الأعمال، والعمل على إيجاد المزيد من الفرص الاستثمارية التي من شأنها أن تساهم في تعزيز قدراتها التنافسية . وعليه يهدف البحث بشكل أساسي إلى معرفة موقع سورية ضمن مؤشرات التنافسية وفق للتقارير الدولية، مع إبراز ترتيبها مقارنة ببقية الدول العربية. In light of the rapid developments witnessed by the world of globalization and integration to the global economy and large developments in information and communications technology, taking the competitive concept widely watched, and the developing countries have taken, including Arab and positioning themselves for the Twins and these developments for the benefit of private pursuing policies and reforms that create habitat advantages Economic appropriate to enhance their competitiveness in an open world to trade and to foreign investment. On this basis, Syria has adopted the concept of competitiveness in order to raise the level of performance of public institutions and the business sector, and work to create more investment opportunities that would contribute to enhance their competitiveness. Find it and mainly aimed at the Syrian site within the competitive indicators according to international reports, highlighting the ranking compared to other Arab countries.